Thomas A. Edison : young inventor - Guthridge, Sue, 1918-; Wood, Wallace (Indianapolis : Bobbs-Merrill, 1959)
A biography focusing on the childhood of the inventor who patented m ore than 1,100 inventions in sixty years, among them the electric light and the phonograph.
Reprint. Originally published: Tom Edison, boy inventor. Indianapoli s : Bobbs-Merrill, [1947]
Keywords: Edison, Thomas A. -- 1847-1931 -- Juvenile literat ure; Edison, Thomas A. -- 1847-1931.; Inventors -- United States -- Biography -- Juvenile literature; Inventors